Organic Food Products : A Study on Perceptions of Indian Consumers - Balaji, Vedha; Injodey, Joseph I. (Indian Journal of Marketing, 2017)
Organic food products are popular across Europe and United States of America. Asia is not far behind with India being a prominent player. The concept of organic food products is not new to Indian farmers. However, there is not much of a consumption taking place domestically despite the fact that India is one of the top 10 players in the world when it comes to the number of farmers engaged in organic cultivation. This study was conducted to understand the factors of consumer perception towards organic food products. The study covered both primary investigation and secondary literature review. Data was collected with the help of a structured questionnaire and was analyzed using percentage analysis and factor analysis to identify the factors of consumer perception.